Competitiveness and Logistics Performance Index: How does the infrastructure pillar perform in ASEAN countries? - Azwardi, Azwardi; Fuadah, Luk Luk; Syathiri, Ahmad (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
This paper examines the impact of strategic sub-components of the Global Competitiveness Index (GCI) on the Logistics Performance Index (LPI), positing a correlation between the LPI and selected GCI factors, specifically within the infrastructure domain—namely, the indicators of Road Quality, Rail Service Efficiency, Port Efficiency, Air Transport Efficiency, and Electrification. The objective is to identify which indicators within the infrastructure sector most significantly affect the Logistics Performance Index. In this study, the LPI is the dependent variable, while the five previously mentioned competitiveness indicators act as independent variables. Top of Form A panel data regression analysis was employed to evaluate how these independent variables influence the dependent variable. The data for this study were derived from the World Bank, specifically the LPI of the World Bank and the World Economic Forum, covering countries in the ASEAN region from 2012 to 2020. The findings indicate that, among the five indicators, Port Efficiency significantly impacts the Logistics Performance Index in the ASEAN region. Furthermore, both Air Transportation Efficiency and Electrification significantly influence the Logistics Performance Index. Conversely, Road Quality and Rail Service Efficiency do not significantly affect the Logistics Performance Index in the ASEAN region.